Super-folding-resistant aluminized transfer film as well as preparation method and application thereof
By adding modified nano-silica grafted polyacrylic acid to PET base film, the problems of insufficient folding resistance and tensile strength of aluminized transfer film are solved, achieving super folding resistance and reusability of the film.
Patent Information
- Application Number
- CN202511137976.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-14
- Publication Date
- 2025-11-14
AI Technical Summary
When existing aluminized transfer films are applied to packaging materials on PET base films, their folding resistance and tensile strength are insufficient, causing the coating to easily crack when frequently opened, closed, or bent, thus affecting the integrity of the packaging.
By surface-modifying nano-silica and adding it to PET base film raw materials, modified nano-silica grafted polyacrylic acid is formed, which enhances the folding resistance and tensile strength of the film.
Modified nano-silica enhances the folding resistance and tensile strength of the membrane through the synergistic effect of rigid particles and flexible chains, reduces substrate fatigue fracture, and enables the membrane to be reused.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of packaging technology, specifically relating to an ultra-resilient aluminum-plated transfer film, its preparation method, and its application. Background Technology
[0002] There are two common approaches to traditional metallized transfer film preparation techniques. One approach involves coating a specific coating onto the surface of a plastic film, such as PET, drying it, and then performing a vacuum metallization process. The film is then laminated with a substrate, and finally the plastic film is peeled off to transfer the metallized layer onto the substrate. The other approach involves first treating the surface of the plastic film to increase its surface energy, then directly metallizing the treated film surface, and finally laminating it with a substrate and peeling off the film to achieve the transfer. However, existing aluminized transfer film technologies have many obvious drawbacks. When transfer films are applied to packaging materials, the folding resistance and tensile strength of PET materials in traditional packaging are relatively poor. When the PET base film is peeled off, the functional coatings such as the release coating layer, laser graphic layer, and aluminized layer left on the packaging surface are prone to developing micro-cracks at the stress concentration bending points when the packaging material is frequently opened and closed or subjected to external bending forces. With the increase of usage, the cracks will gradually expand, and in severe cases, they may even completely break, destroying the integrity of the packaging. Therefore, it is very important to improve the folding resistance and tensile strength of PET materials. Summary of the Invention
[0003] To address the shortcomings mentioned in the background art, the present invention aims to provide an ultra-resistant aluminum-plated transfer film, its preparation method, and its application. By modifying the surface of nano-silica and adding it to PET base film raw materials, the folding resistance and tensile strength of the aluminum-plated transfer film are effectively improved, making it reusable and in line with the concept of green environmental protection.
[0004] The objective of this invention can be achieved through the following technical solutions: A super-resistant aluminum transfer film, its preparation method and application, comprising the following raw materials in parts by weight: 85-90 parts PET resin, 2-5 parts lubricant, 0.5-1.5 parts UV absorber, 1-2 parts modified nano silica, and 0.3-0.5 parts antioxidant; wherein the modified nano silica is nano silica grafted with polyacrylic acid.
[0005] More preferably, the lubricant is one or more of butyl stearate, stearamide, and talc; the ultraviolet absorber is one or more of 2-hydroxy-4-methoxybenzophenone, ethyl 2-cyano-3,3-diphenylacrylate, and phenyl 4-tert-butylsalicylate; and the antioxidant is one or more of antioxidant 1010, antioxidant 1076, and antioxidant 168.
[0006] More preferably, the method for preparing modified nano-silica includes the following steps: A1. Take nano-silica, soak it in a 5% dilute hydrochloric acid solution for 1-2 hours, stir it magnetically at a speed of 200-300 r / min, filter it, wash it with deionized water, and dry it in a forced-air dryer at 70-80℃ for 3-4 hours for later use. A2. Add the pretreated nano-silica to anhydrous ethanol, disperse it in an ultrasonic cleaner for 1-2 hours, add silane coupling agent dropwise, heat to 80-90℃, continue stirring the reaction for 2-3 hours after the addition is complete, evaporate the solvent after the reaction is complete, transfer the obtained powder to a vacuum oven to obtain surface alkylated silica. A3. Add alkylated silica to deionized water, sonicate for 20-30 min, then transfer to a four-necked flask. Dissolve the initiator ammonium persulfate in deionized water, then add acrylic monomer dropwise over a time of 20-30 min. Continue the reaction for 3-6 h after the addition is complete. After the reaction is complete, filter under vacuum, wash the filter cake with deionized water, and dry it in a forced-air drying oven at 100-120℃ for 2-3 h to obtain nano-silica grafted polyacrylic acid.
[0007] More preferably, the acrylic monomer is methyl methacrylate, the amount of ammonium persulfate initiator is 2% of the mass of the acrylic monomer, and the mass ratio of acrylic monomer to alkylated silica is 1:1.2.
[0008] A method for preparing the super-rebound resistant aluminum transfer film includes the following steps: S1. Weigh the PET resin, lubricant, UV absorber, modified nano silica, and antioxidant according to the above weight proportions, and place them in a high-speed mixer for mixing. Set the mixer speed to 800-1200 r / min and the mixing temperature to 80-100℃. Under these conditions, ensure that the raw materials are fully contacted and mixed evenly to obtain a mixture. Add the mixture to a two-roll plasticizer for compounding. Control the plasticizing temperature to 160-180℃ to allow the PET resin to gradually melt and obtain a composite material. The melt flowing from the extruder die is rapidly cooled and solidified into a thick sheet on the surface of the casting roller. The die temperature is controlled at 200-300℃. Stretch the thick sheet into a base film on a longitudinal stretching machine at a stretching temperature of 90-110℃. Then, stretch the longitudinally stretched base film laterally. After shaping and cooling, the stretched base film is obtained as a PET base film. S2. Create a master mold with holographic grating patterns and laser graphic patterns, and electroform it to form a molding work plate. Coat the upper surface of the PET base film with a release coating, and after drying, form a release coating layer. Install the molding work plate on the molding roller. Coat the surface of the PET base film with the release coating layer with a layer of UV-curable embossing coating, so that the coating layer is in close contact with the molding roller with the molding work plate. Control the pressure to fill the grooves on the molding work plate with UV-curable embossing coating, and then cure the coating layer under UV light to form a laser graphic layer. This process uses UV curing for rapid molding and avoids the impact of high temperature on the folding resistance of the base film. S3. On the surface of the laser graphic layer, a magnetron sputtering aluminum coating device is used to uniformly form an aluminum coating layer on a high-purity aluminum target through sputtering. The aluminum coating layer is tightly bonded to the laser graphic layer and is evenly distributed, which helps to maintain the ultra-folding resistance of the transfer film. Under the traction of the guide roller, the film material after the above treatment maintains a stable tension as a whole, ensuring the integrity of each layer structure, and finally obtaining an ultra-folding resistant aluminum-coated transfer film including a PET base film, a release coating layer, a laser graphic layer and an aluminum coating layer.
[0009] The beneficial effects of this invention are: By surface-modifying nano-silica and adding it to PET base film raw materials, the modified nano-silica works synergistically through the rigid particles and flexible chains: the rigid nano-silica disperses bending stress and reduces substrate fatigue fracture, while the grafted polyacrylic acid chains form physical entanglement with PET molecular chains, enhancing interfacial bonding and effectively improving the folding resistance and tensile strength of the film material. It is not easy to break when peeled off and can be repeatedly recycled, in accordance with the concept of sustainable development. Detailed Implementation
[0010] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0011] Example 1: A method for preparing modified nano-silica, comprising the following steps: A1. Take 80g of nano-silica, soak it in 400mL of 5% hydrochloric acid solution for 1.5h, stir magnetically at 200r / min, filter, wash with deionized water, and dry in a forced-air dryer at 75℃ for 3.5h for later use. A2. Add the pretreated nano-silica to anhydrous ethanol, disperse it in an ultrasonic cleaner for 1.5 h, add 2.4 g of silane coupling agent, heat to 85 °C, and continue stirring the reaction for 2.5 h after the addition is complete. After the reaction is complete, evaporate the solvent, transfer the obtained powder to a vacuum oven to obtain surface alkylated silica. A3. Add alkylated silica to deionized water, sonicate for 25 min, then transfer to a four-necked flask. Dissolve 0.24 g of initiator ammonium persulfate in deionized water, then add 12 g of acrylic acid monomer. Control the addition time at 25 min. After the addition is complete, continue the reaction for 5 h. After the reaction is complete, vacuum filter, wash the filter cake with deionized water, and dry it in a forced-air drying oven at 110 ℃ for 2.5 h to obtain nano-silica grafted polyacrylic acid.
[0012] Example 2: An ultra-resilient aluminum transfer film, comprising the following raw materials in parts by weight: 90 parts PET resin, 2 parts butyl stearate, 1.5 parts 2-hydroxy-4-methoxybenzophenone, 1 part modified nano silica, and 0.5 parts antioxidant 1010; the modified nano silica is the nano silica grafted polyacrylic acid prepared in Example 1.
[0013] The preparation method of the above-mentioned super fold-resistant aluminum transfer film includes the following steps: S1. Weigh the PET resin, lubricant, UV absorber, modified nano silica, and antioxidant according to the above weight proportions, and place them in a high-speed mixer for mixing. Set the mixer speed to 1200 r / min and the mixing temperature to 80℃. Under these conditions, ensure that the raw materials are fully contacted and mixed evenly to obtain a mixture. Add the mixture to a two-roll plasticizer for kneading. Control the plasticizing temperature to 180℃ to allow the PET resin to gradually melt and obtain a composite material. The melt flowing out from the extruder die is rapidly cooled and solidified into a thick sheet on the surface of the casting roller. The die temperature is controlled at 200℃. Stretch the thick sheet into a base film on a longitudinal stretching machine at a stretching temperature of 110℃. Then, stretch the longitudinally stretched base film laterally. After shaping and cooling, the stretched base film is used to obtain a PET base film. S2. Create a master mold with holographic grating patterns and laser graphic patterns, and electroform it to form a molding work plate. Coat the upper surface of the PET base film with a release coating, and after drying, form a release coating layer. Install the molding work plate on the molding roller. Coat the surface of the PET base film with the release coating layer with a layer of UV-curable embossing coating, so that the coating layer is in close contact with the molding roller with the molding work plate. Control the pressure to fill the grooves on the molding work plate with UV-curable embossing coating, and then cure the coating layer under UV light to form a laser graphic layer. This process uses UV curing for rapid molding and avoids the impact of high temperature on the folding resistance of the base film. S3. On the surface of the laser graphic layer, a magnetron sputtering aluminum coating device is used to uniformly form an aluminum coating layer on a high-purity aluminum target through sputtering. The aluminum coating layer is tightly bonded to the laser graphic layer and is evenly distributed, which helps to maintain the ultra-folding resistance of the transfer film. Under the traction of the guide roller, the film material after the above treatment maintains a stable tension as a whole, ensuring the integrity of each layer structure, and finally obtaining an ultra-folding resistant aluminum-coated transfer film including a PET base film, a release coating layer, a laser graphic layer and an aluminum coating layer.
[0014] Example 3: A method for preparing an ultra-resilient aluminum transfer film, comprising the following raw materials in parts by weight: The mixture consisted of 85 parts PET resin, 4 parts stearamide, 1 part ethyl 2-cyano-3,3-diphenyl acrylate, 1 part modified nano silica, and 0.4 parts antioxidant 1076. The modified nano silica was the nano silica grafted polyacrylic acid prepared in Example 1.
[0015] The preparation method of the super-rebound refractory aluminum-plated transfer film includes the following steps: S1. Weigh the PET resin, lubricant, UV absorber, modified nano silica, and antioxidant according to the above weight proportions, and place them in a high-speed mixer for mixing. Set the mixer speed to 800 r / min and the mixing temperature to 100℃. Under these conditions, ensure that the raw materials are fully contacted and mixed evenly to obtain a mixture. Add the mixture to a two-roll plasticizer for kneading. Control the plasticizing temperature to 160℃ to allow the PET resin to gradually melt and obtain a composite material. The melt flowing out from the extruder die is rapidly cooled and solidified into a thick sheet on the surface of the casting roller. The die temperature is controlled at 300℃. Stretch the thick sheet into a base film on a longitudinal stretching machine at a stretching temperature of 90℃. Then, stretch the longitudinally stretched base film laterally. After shaping and cooling, the stretched base film is used to obtain a PET base film. S2. Create a master mold with holographic grating patterns and laser graphic patterns, and electroform it to form a molding work plate. Coat the upper surface of the PET base film with a release coating, and after drying, form a release coating layer. Install the molding work plate on the molding roller. Coat the surface of the PET base film with the release coating layer with a layer of UV-curable embossing coating, so that the coating layer is in close contact with the molding roller with the molding work plate. Control the pressure to fill the grooves on the molding work plate with UV-curable embossing coating, and then cure the coating layer under UV light to form a laser graphic layer. This process uses UV curing for rapid molding and avoids the impact of high temperature on the folding resistance of the base film. S3. On the surface of the laser graphic layer, a magnetron sputtering aluminum coating device is used to uniformly form an aluminum coating layer on a high-purity aluminum target through sputtering. The aluminum coating layer is tightly bonded to the laser graphic layer and is evenly distributed, which helps to maintain the ultra-folding resistance of the transfer film. Under the traction of the guide roller, the film material after the above treatment maintains a stable tension as a whole, ensuring the integrity of each layer structure, and finally obtaining an ultra-folding resistant aluminum-coated transfer film including a PET base film, a release coating layer, a laser graphic layer and an aluminum coating layer.
[0016] Example 4: Ultra-resilient aluminum-plated transfer film. The above preparation method includes the following raw materials in parts by weight: The mixture contained 85 parts of PET resin, 5 parts of talc, 0.5 parts of 4-tert-butylsalicylic acid phenyl ester, 2 parts of modified nano silica, and 0.3 parts of antioxidant 168; the modified nano silica was the nano silica grafted polyacrylic acid prepared in Example 1.
[0017] S1. Weigh the PET resin, lubricant, UV absorber, modified nano silica, and antioxidant according to the above weight proportions, and place them in a high-speed mixer for mixing. Set the mixer speed to 1000 r / min and the mixing temperature to 90℃. Under these conditions, ensure that the raw materials are fully contacted and mixed evenly to obtain a mixture. Add the mixture to a two-roll plasticizer for kneading. Control the plasticizing temperature to 170℃ to allow the PET resin to gradually melt and obtain a composite material. The melt flowing out from the extruder die is rapidly cooled and solidified into a thick sheet on the surface of the casting roller. The die temperature is controlled at 250℃. Stretch the thick sheet into a base film on a longitudinal stretching machine at a stretching temperature of 100℃. Then, stretch the longitudinally stretched base film laterally. After shaping and cooling, the stretched base film is used to obtain a PET base film. S2. Create a master mold with holographic grating patterns and laser graphic patterns, and electroform it to form a molding work plate. Coat the upper surface of the PET base film with a release coating, and after drying, form a release coating layer. Install the molding work plate on the molding roller. Coat the surface of the PET base film with the release coating layer with a layer of UV-curable embossing coating, so that the coating layer is in close contact with the molding roller with the molding work plate. Control the pressure to fill the grooves on the molding work plate with UV-curable embossing coating, and then cure the coating layer under UV light to form a laser graphic layer. This process uses UV curing for rapid molding and avoids the impact of high temperature on the folding resistance of the base film. S3. On the surface of the laser graphic layer, a magnetron sputtering aluminum coating device is used to uniformly form an aluminum coating layer on a high-purity aluminum target through sputtering. The aluminum coating layer is tightly bonded to the laser graphic layer and is evenly distributed, which helps to maintain the ultra-folding resistance of the transfer film. Under the traction of the guide roller, the film material after the above treatment maintains a stable tension as a whole, ensuring the integrity of each layer structure, and finally obtaining an ultra-folding resistant aluminum-coated transfer film including a PET base film, a release coating layer, a laser graphic layer and an aluminum coating layer.
[0018] Comparative Example 1: A method for preparing an ultra-resilient aluminum transfer film, the composition and preparation are the same as in Example 4, except that no modified nano-silica is added.
[0019] Performance testing The super fold-resistant aluminum-plated transfer films prepared in Examples 2-4 and Comparative Example 1 were tested for various properties under different conditions. The fold resistance was tested according to GB / T2679.5-1995, and the test strips were all rectangular. The tensile strength was tested according to GBT1040.4-2006, and the test strips were rectangular. The data are shown in Table 1 below.
[0020] Table 1 Performance Testing of Super Fold-Resistant Aluminum-Coated Transfer Film
[0021] As can be seen from the data in Table 1, Examples 2, 3, and 4, which contain modified nano-silica, show significant differences in folding resistance and tensile strength compared to Comparative Example 1, which does not contain modified nano-silica. The folding resistance and tensile strength of the film material in Examples 2-4 are improved after the addition of modified nano-silica, with Example 4 showing the best effect. This fully demonstrates that modified nano-silica can effectively enhance the folding resistance and tensile strength of the film material, making the PET base film less prone to breakage during peeling and allowing for repeated use.
[0022] In summary, the addition of modified nano-silica has a positive effect on improving the folding resistance and tensile strength of the ultra-fold-resistant aluminum-plated transfer film. Among them, the performance improvement in Example 4 is more obvious, further verifying the effectiveness and advantages of using modified nano-silica in this invention.
[0023] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0024] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention.
Claims
1. A super-resistant aluminum transfer film, characterized in that, The product comprises a PET base film, a release coating layer, a laser graphic layer, and an aluminum plating layer. The release coating layer is a special coating applied to the surface of the PET base film and cured after drying. The laser graphic layer is a functional layer with holographic gratings or specific patterns formed on the surface of the release coating layer through a molding process, and is prepared using ultraviolet light-cured imprinted coating. The aluminum plating layer is an aluminum film formed on the surface of the laser graphic layer using a magnetron sputtering process. The PET base film comprises the following raw materials in parts by weight: 85-90 parts PET resin, 2-5 parts lubricant, 0.5-1.5 parts ultraviolet absorber, 1-2 parts modified nano-silica, and 0.3-0.5 parts antioxidant. The modified nano-silica is nano-silica grafted with polyacrylic acid.
2. The ultra-resilient aluminum transfer film according to claim 1, characterized in that, The lubricant is one or more of butyl stearate, stearamide, and talc.
3. The ultra-resilient aluminum transfer film according to claim 1, characterized in that, The ultraviolet absorber is one or more of 2-hydroxy-4-methoxybenzophenone, ethyl 2-cyano-3,3-diphenylacrylate, and phenyl 4-tert-butylsalicylate.
4. The ultra-resilient aluminum transfer film according to claim 1, characterized in that, The antioxidant is one or more of antioxidant 1010, antioxidant 1076, and antioxidant 168.
5. The ultra-resilient aluminum transfer film according to claim 1, characterized in that, The method for preparing the modified nano-silica includes the following steps: A1. Take nano-silica, soak it in a 5% dilute hydrochloric acid solution for 1-2 hours, stir it magnetically at a speed of 200-300 r / min, filter it, wash it with deionized water, and dry it in a forced-air dryer at 70-80℃ for 3-4 hours for later use. A2. Add the pretreated nano-silica to anhydrous ethanol, disperse it in an ultrasonic cleaner for 1-2 hours, add silane coupling agent dropwise, heat to 80-90℃, continue stirring the reaction for 2-3 hours after the addition is complete, evaporate the solvent after the reaction is complete, transfer the obtained powder to a vacuum oven to obtain surface alkylated silica. A3. Add alkylated silica to deionized water, sonicate for 20-30 min, then transfer to a four-necked flask. Dissolve the initiator ammonium persulfate in deionized water, then add acrylic monomer dropwise over a time of 20-30 min. Continue the reaction for 3-6 h after the addition is complete. After the reaction is complete, filter under vacuum, wash the filter cake with deionized water, and dry it in a forced-air drying oven at 100-120℃ for 2-3 h to obtain nano-silica grafted polyacrylic acid.
6. The ultra-resilient aluminum transfer film according to claim 5, characterized in that, The acrylic monomer is methyl methacrylate, the amount of ammonium persulfate initiator is 2% of the mass of acrylic monomer, and the mass ratio of acrylic monomer to alkylated silica is 1:1.
2.
7. A method for preparing an ultra-resilient aluminum transfer film as described in any one of claims 1 to 6, characterized in that, Includes the following steps: S1. Weigh the PET resin, lubricant, UV absorber, modified nano silica, and antioxidant according to the above weight proportions, and place them in a high-speed mixer for mixing. Set the mixer speed to 800~1200 r / min and the mixing temperature to 80~100℃. Under these conditions, ensure that the raw materials are fully contacted and mixed evenly to obtain a mixture. Add the mixture to a two-roll plasticizer for compounding. Control the plasticizing temperature to 160~180℃ to allow the PET resin to gradually melt and obtain a composite material. The melt flowing out from the extruder die is rapidly cooled and solidified into a thick sheet on the surface of the casting roller. The die temperature is controlled at 200~300℃. Stretch the thick sheet into a base film on a longitudinal stretching machine at a stretching temperature of 90~110℃. Then, stretch the longitudinally stretched base film transversely. After shaping and cooling, the stretched base film is obtained as a PET base film. S2. Create a master mold with holographic grating patterns and laser graphic patterns, perform electroforming to form a molding work plate, coat a layer of release coating on the upper surface of the PET base film, and after drying, form a release coating layer. Install the molding work plate on the molding roller, coat a layer of UV-curable embossing coating on the surface of the PET base film with the release coating layer, so that the coating layer is in close contact with the molding roller with the molding work plate, control the pressure to fill the grooves on the molding work plate with the UV-curable embossing coating, and then cure the coating layer under UV light to form a laser graphic layer. This process uses UV curing for rapid molding and avoids the impact of high temperature on the folding resistance of the base film. S3. On the surface of the laser graphic layer, a magnetron sputtering aluminum coating device is used to uniformly form an aluminum coating layer on a high-purity aluminum target through sputtering. The aluminum coating layer is tightly bonded to the laser graphic layer and is evenly distributed, which helps to maintain the ultra-folding resistance of the transfer film. Under the traction of the guide roller, the film material after the above treatment maintains a stable tension as a whole, ensuring the integrity of each layer structure, and finally obtaining an ultra-folding resistant aluminum-coated transfer film including a PET base film, a release coating layer, a laser graphic layer and an aluminum coating layer.
8. The application of the ultra-diffusive aluminized transfer film as described in any one of claims 1 to 6 in transfer-metallized packaging paper, characterized in that, PET base film has high folding resistance and high tensile strength, is not easily broken when peeled, and can be reused.